Drug problem : social and economic effects - policy options for the Caribbean. - Sanders, Ronald (1990)
Discusses the problems of corruption and the threat to democratic institutions; drug abuse and a rise in crime; diversion of scarce resources to fight drug trafficking and drug abuse; and threats to the sovereign authority of Caribbean states by the manner in which the United States administration has sought to deal with the interdiction of drug traffickers and money laundering in the region.